ANALISIS KEMAMPUAN BERFIKIR KREATIF MATEMATIS SISWA SMP KELAS VIII PADA MATERI BANGUN RUANG - Abidin, Jenal; Rohaeti, Euis Eti; Afrilianto, M (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to examine and analyze the students' creative thinking ability. The population in this study is the students of grade VIII junior high school in one of the schools in Karawang. This classroom action research is planned to consist of 2 (two) cycles. Firstly given initial tests with a view to know the initial ability of students and related to the material wake up space. In the first cycle, the remaining able to answer the problem well reach 36.6%. From the results of tests in the first cycle can be said the ability of creative thinking students is still low.